Los procesos cognitivos básicos de atención y memoria y la comprensión lectora en estudiantes de primer ciclo de la carrera de Agronomía de la Facultad Agropecuaria y de Recursos Naturales Renovables de la Universidad Nacional de Loja, 2024. - Vega Palacios, Nicole Alexandra (2024)
The objective of the research was to analyze the relationship between the basic cognitive processes of attention, memory and reading comprehension between the basic cognitive processes of attention and memory and reading comprehension. The study was done with a quantitative, correlational and cross-sectional approach, with a non- experimental design. The instruments applied were the D2 attention test, the Reynolds intelligence scale (RIAS) and the instrument to evaluate reading comprehension in university students (ICLAU), with a sample of 27 first cycle students of the Agronomy career of the “Universidad Nacional de Loja”, to analyze the correlation that exists between the variables in the computer program Excel and were interpreted with Pearson's lineal correlation scale. The results showed that 77.78% present a low level of attention and 3.7% are at a high level. Respect to memory, 37.04% present a low level, 48.15% a medium level and 14.81% are at a high level. In reading comprehension, 7.41% of the students present a low level, while more than half, 77.78% are at a medium level and 14.81% at a high level. The correlation between attention and reading comprehension shows a value of +0.24, while the correlation between memory and reading comprehension shows a value of +0.34, in both it is concluded that there is an average positive correlation between the cognitive processes and reading comprehension.